Extreme Temporalities in Experimental Electroacoustic Music and Sound Art - Blake Stevens (Musica Docta)
This essay explores the pedagogical value of teaching forms of electroacoustic music and sonic art such as drone composition and site-specific sound installations that exceed human perceptual capacities and that resist attempts at documentation and representation. It suggests that encounters with forms of “extreme temporality,” borrowing a term from Hans Ulrich Gumbrecht, may be placed in constructive dialogue with the implicit models of ‘regular’ time and musical duration that often shape the listening habits of students. These encounters invite the crossing of the boundaries separating ‘music’ from ‘sound art’ and ‘works’ from ‘events’. They also invite the exploration of alternate forms of listening, shaped by sonic experimentation with modes of embodied experience and consciousness, that challenge the ready availability and ‘closure’ of most digital musical artifacts.